Perfomance study and propagation measurement for indoor wireless link at college 17, UTM [electronic resource] - 191798 Mohd. Hadi Abd. Rani; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik -Telekomunikasi)) - Universiti Teknologi Malaysia, 2007